Regulatory role of endogenous and exogenous fibroblast growth factor 1 in the cardiovascular system and related diseases. (July 2021) - Xiao, Mengjie; Tang, Yufeng; Wang A, Jie; Wang B, Jie; Lu, Guangping; Guo, Yuanfang; Zhang, Jingjing; Gu, Junlian
Abstract: Fibroblast growth factor 1 (FGF1) has a critical regulatory role in the development of the cardiovascular system (CVS) and is strongly associated with the progression or treatment of cardiovascular diseases (CVDs). However, the regulatory mechanisms of FGF1 in CVS and CVDs have not yet been fully elucidated. Therefore, this review article summarized the existing literature reports on the role of FGF1 in CVS under physiological and pathological conditions. First, the expression and physiological functions of endogenous FGF1 is fully demonstrated. Then, we analyzed the role of exogenous FGF1 in normal CVS and related pathological processes. Specifically, the potential signaling pathways might be mediated by FGF1 in CVDs treatment is discussed in detail. In addition, the barriers and feasible solutions for the application of FGF1 are further analyzed. Finally, we highlight therapeutic considerations of FGF1 for CVDs in the future. Thus, this article may be as a reference to provide some ideas for the follow-up research. Graphical Abstract: ga1